Mental wellbeing among urban young adults in a developing country: A Latent Profile Analysis - Nguyen, Thao Thi Phuong; Nguyen, Tham Thi; Dam, Vu Trong Anh; Vu, Thuc Thi Minh; Do, Hoa Thi; Vu, Giang Thu; Tran, Anh Quynh; Latkin, Carl A.; Hall, Brian J.; Ho, Roger C. M.; Ho, Cyrus S. H. (Frontiers in Psychology, 2022)
Introduction This study aimed to explore the mental wellbeing profiles and their related factors among urban young adults in Vietnam. Methods A cross-sectional study was conducted in Hanoi, which is the capital of Vietnam. There were 356 Vietnamese who completed the Mental Health Inventory-5 (MHI-5) questionnaire. The Latent Profile Analysis (LPA) was used to identify the subgroups of mental wellbeing through five items of the MHI-5 scale as the continuous variable. Multinomial logistic regression was used to determine factors related to subgroups. Results Three classes represented three levels of MHI-5 score, which included “Poor mental health,” “Fair mental health,” and “Good mental health,” were, respectively, 14.3, 46.6, and 39.0%. Compared to a low household economy, participants with an average household economy had 2.11 and 4.79 times higher odds of being in a good mental health class relative to fair and poor mental health classes. Respondents with more than two acute symptoms had 3.85 times higher odds of being in a good mental health class relative to a poor mental health class, as compared to those without acute symptoms. Regarding the measurement of the Perceived Social Support Scale (MSPSS), people having support from their family had 1.80 and 2.23 times higher odds of being in classes of fair and good mental health relative to the poor mental health class; and participants having friend support also had 1.87 times higher odds of being in a good mental health class compared with the fair mental health class, as the MSPSS score increased by 1 unit. People with Rosenberg’s self-esteem scale increased by 1 score, those who had 1.17, 1.26, and 1.47 times higher odds of being in a good compared to fair mental health class, fair compared to poor mental health class, and good compared to poor mental health class, respectively. Conclusion Our findings were given to promote a new classification method for mental health screening among the general population. The current findings could be used as evidence to develop policies and plans that focus on encouraging early screening for mental health problems among the general young population in the future.